DETERMINAN PAJAK PENGHASILAN BADAN PADA PERUSAHAAN SEKTOR INDUSTRI BARANG DAN KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Amos Saptari Marnala; Ronny Buha Sihotang (Jurnal Saintifik, 2023)
One of the subjects that receives the most research is profitability. However, the outcomes of some studies vary. The goal of this study is to learn more about some factors that could have a big impact on profitability. The profitability of companies in the manufacturing sector that are listed on the Indonesia Stock Exchange (BEI) from 2016 to 2020 is the subject of this investigation, which looks at the effects of both internal and external factors. Multiple linear regression and secondary data are used in this study's quantitative approach. Firm size, age, liquidity, capital structure, firm growth, capital intensity, and a macroeconomic indicator are the independent variables in this study, with profitability serving as the dependent variable. Within the scope of the study, 789 observations were utilized. In three years, these observations covered 263 businesses. Profitability is significantly impacted by firm age, size, liquidity, growth, capital intensity, and macroeconomic indicators. Profitability is found to be negatively impacted by capital structure.